Sequential ordering of crane service requests considering the pending times of the requests: An approach based on game theory and optimization techniques - Monghasemi, Shahryar; Nikoo, Mohammad Reza; Adamowski, Jan (Elsevier, 2016)
Progress on a construction project can be derailed if its timetable is not met. Should a crane service request become overdue it may be preferable to minimize the pending time of the service request rather than minimize the crane's overall travel time. A novel approach was developed which minimizes and distributes the pending times uniformly, using a least deviation method to prioritize possible sequences according to the pending time for each requested crane service. An improved harmony search based on the power index method was then used to search for the sequence which led to the least deviation of priorities from their mean values. The efficiency of the proposed method was tested on a benchmark from the literature which involved solving 10, 50 or 100 service request problems. The proposed method achieved distribution of the deviation of pending times by approximately 40%, 50% and 10%, respectively. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Tower crane; Optimization; Least deviation method; Sequential ordering; Improved harmony search; Power index; Fuzzy preference relation